Migration and technical efficiency in cereal production: Evidence from Burkina Faso - Wouterse, Fleur Stephanie (International Food Policy Research Institute, 2008)
This paper uses data envelopment analysis and new data from Burkina Faso to test the impact of intercontinental and continental migration on technical efficiency in the production of two cereals—millet and sorghum—by rural households. Econometric evidence supports our theoretical expectation that the impact of emigration varies by migrant destination. I find evidence of a positive relation between continental migration and technical efficiency and a negative relation between intercontinental migration and technical efficiency. In an imperfect market environment, continental migration is associated with greater efficiency because it removes a male labor surplus; explanations for the negative relationship between intercontinental migration and technical efficiency should be sought in a surplus of female labor supply. Overall, findings suggest that migration does not lead to a transformation of cereal production from traditional to modern, because in an imperfect market environment, liquidity received in the form of remittances cannot compensate for labor shortfalls.